Penggunaaan Model Team Games Tournament (TGT) pada Pembelajaran Matematika untuk Meningkatkan Kerja sama dan Hasil Belajar pada Siswa Kelas 1 SDN Bugangan 03 (Jurnal Simki Pedagogia, 2024)
This research was motivated by providing stimulation to grade 1 students at SDN Bugangan 03 regarding cooperation and improving learning outcomes for students. The aim of this research is to stimulate the ability to collaborate between grade 1 students so as to create an environment that cares for each other and is able to work together and the impact of collaboration between students. This research uses a qualitative approach with descriptive analysis. The research results show that by learning using the Team Games Tournament (TGT) method, students become more enthusiastic in participating in the learning process because of the competition created to motivate students to compete with each other. Apart from that, students are also more active in solving existing problems. This change in attitude can be seen from the results of the attitude assessment carried out by the teacher. Based on the results of the tests carried out, it shows that the learning outcomes obtained by students are better. This can be seen from the results of evaluations carried out by students which are getting better and improving.